Sustainable fabrication of copper nanoparticles: a potent and affordable candidate for water treatment, water disinfection, antioxidant activity and theranostic agent - Sinha, Tanur; Adhikari, Partha Pradip; Bhandari, Vinay M. (ChemistrySelect, 2022)
This study reports a simple, green, and large-scale biosynthetic fabrication of spherical copper nanoparticles (Cu NPs), approximate 28 nm, using the aqueous extracts of Diaplazium esulentum (Retz.) Sw. fern. Characterization was carried out for morphology, size, elemental analysis, crystallinity and for identification of functionalities responsible for reduction and stabilization. Extraordinary remediation efficiency was obtained for the developed Cu NPs for the elimination of two industrially important pollutants; Methyl Violet 6B and Methylene Blue (greater than 92 % within 150 mins). A mechanism was postulated for the process using the data on the identification of NPs and also spent NPs apart from degraded products. Furthermore, the Cu NPs revealed excellent antibacterial activity against gram positive bacteria: Staphylococcus aureus, Streptococcus pneumonia and Bacillus subtilis, as well as gram negative bacteria: Pseudomonas aeruginosa, Escherichia coli and potential action against fungal strains; Aspergillus niger and Candida albicans. Additionally, the assay depicted that Cu NPs has fairly decent radical scavenging activity with IC50 value 2.11 mM. Moreover, the Cu NPs were found to exhibit profound anticancerous activity against two human cancer line cells. The present research work has implications for exploitation of DE fern extract for the development of Cu NPs and their numerous applications ranging from pollutants removal to antibacterial, antifungal, antioxidant and anticancerous agents.
Keywords: Anticancer; antifungal; Antimicrobial; Antioxidant; Photodegradation and Phytosynthesis